(untitled) (Economics and region, 2024)
The article, based on the analysis of domestic and foreign literature and practice and summarizing the personal experience of the authors, singles out modern problems, approaches and trends of city management. The study of this process of public administration is defined as relevant, given its high social importance and the need for constant modernization. The research hypothesis is based on the position of the central place of citizens united in a territorial community in the processes of public administration, which is determined by a combination of external development trends and influencing factors, taking into account local specifics. The authors noted that global trends in the development of cities, and accordingly, trends in improving their public management, are formed by external processes of globalization, glocalization, informatization, etc. (exogenous factors) and internal (endogenous factors). Therefore, it is emphasized the need to take into account both the trend towards universalization and local specifics, which should become the basis for sustainable development of cities, when developing city development strategies. The goal of public authorities should be to create an endogenous vision of the future of the designated territories, taking into account local resources, values and own development paths, taking into account global processes and requirements of Europeanization. It was noted that this can only be achieved with the help of the public. Economic factors and the impact of European integration are also considered key in the preparation of strategies for the development of Ukrainian cities. State regulation of this process is considered essential. It was noted that the actualization of the development of strategies of Ukrainian cities under the influence of international aid programs is a guarantee of receiving investments. It is emphasized the need to take into account the requirements of sustainable development, especially taking into account the influence of the military factor. Taking into account the general trends and features of development is clearly manifested in the problems, the list of which largely depends on the specifics of regional development. These problems are the result of: the historical past, the current state of the country and its regions, the level of the country’s entry into the global market, the lack of sufficient resources to solve the problems, etc.The main problems of urban development (ecological, economic, social, cultural, etc.) are systematized on the basis of Ukrainian and Polish experience. The complexities of urban development are highlighted as inevitable problems of growth that appear as a result of the achievements of modern technologies. The trend of shifting the focus of efforts from solving the problems of megalopolises to the problems of the development of small towns, noticed by practitioners and experts even before the war, is mentioned separately: self-identification; vulnerability; dependence; lack of strategic thinking and communication; difficult heredity, etc. However, as a result of the war, population concentration in several large cities is possible. The specificity of Ukrainian cities, related to the impact of the war, increases the differentiation according to certain directions of development: the search for investments, reconstruction, revitalization, special attention to labor market processes, ensuring barrier-free access, etc. It is important not to dwell on problems, but to see them as a challenge and strive to find a worthy answer.